Biomedical Applications and Toxicity of Nanomaterials - Mohanan, P. V.; Kappalli, Sudha (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book covers the recent trends on the biological applications of nanomaterials, methods for their preparation, and techniques for their characterization. Further, the book examines the fundamentals of nanotoxicity, methods to assess the toxicity of engineered nanomaterials, approaches to reduce toxicity during synthesis. It also provides an overview of the state of the art in the application of Artificial intelligence-based methodologies for evaluation of toxicity of drugs and nanoparticles. The book further discusses nanocarrier design, routes of various nanoparticle administration, nano based drug delivery systems, and the toxicity challenges associated with each drug delivery method. It presents the latest advances in the interaction of nanoparticles with the cellular environment and assess nanotoxicity of these engineered nanoparticles. The book also explores the comparative and mechanistic genotoxicity assessment of the nanomaterials. This book is useful source of information for industrial practitioners, policy makers, and other professionals in the fields of toxicology, medicine, pharmacology, food, and drugs.
Chapter 1. Macroporous cryogel-based systems for water treatment applications and Safety: nanocomposite-based cryogels and bacteria-based bioreactors -- Chapter 2. One dimensional Semiconducting Nanomaterials: Toxicity and Clinical Applications -- Chapter 3. Prospects of Safe use of Nanomaterials in Biomedicalapplications -- Chapter 4. Hyaluronic acid-based nanotechnologies for delivery and treatment -- Chapter 5. Theranostics nanomaterials for safe cancer treatment -- Chapter 6. Cardiovascular safety assessment of new chemical entities: current perspective and emerging technologies -- Chapter 7. Toxicology of pharmaceutical products during drug development -- Chapter 8. Safety and Risk assessment of food items -- Chapter 9. Non toxic Natural products as regulators of tumour suppressor gene function -- Chapter 10. Advancements in the safety of Plant medicine: Back to nature -- Chapter 11. Chemicals and their interaction in the aquaculture system -- Chapter 12. Zebrafish as a biomedical model to define developmental origins of chemical toxicity -- Chapter 13. Green synthesis of non toxic nanoparticles -- Chapter 14. Synthesis, characterisation and safety of titanium oxide nanoparticles -- Chapter 15. Characterisation of non toxic nanomaterials for biological applications -- Chapter 16. Toxicity assessment of nanoparticle -- Chapter 17. Safety of nanoparticles: emphasis on antimicrobial properties -- Chapter 18. Quantum dots for imaging and its safety -- Chapter 19. Genotoxicity evaluation of nanosized materia -- Chapter 20. Scaffoldmaterials and toxicity -- Chapter 21 Biological Safety and Cellular interactions of nanoparticles -- Chapter 22. Role of artificial intelligence in the toxicity prediction of drugs -- Chapter 23. Chemicals and rodent models for the safety study of alzheimer's disease -- Chapter 24. Mitochondria-targeted liposomal delivery in Parkinson's disease: safety concerns -- Chapter 25. Routes of Nano-drug Administration and Nano-based drug delivery system and toxicity -- Chapter 26. Green Synthesised silver nanoparticles phytotoxicity and applications in agriculture: An overview -- Chapter 27 status of safety concerns of microplastic detection strategies -- Chapter 28. Impact of insecticides on man and environment.
Keywords: Pharmacology; Nanobiotechnology; Nanomedicine; Pharmacology; Nanobiotechnology; Nanomedicine and Nanotoxicology